Inhibition of the Renin–Angiotensin System Improves Hemodynamic Function of the Diabetic Rat Heart by Restoring Intracellular Calcium Regulation - Krisztina Anna Paulik; Tamás Ivanics; Gábor A. Dunay; Ágnes Fülöp; Margit Kerék; Klára Takács; Zoltán Benyó; Zsuzsanna Miklós (Biomedicines)
Background/Objectives: Disrupted intracellular calcium (Ca2+i) regulation and renin–angiotensin system (RAS) activation are pathogenetic factors in diabetic cardiomyopathy, a major complication of type 1 (T1D) and type 2 (T2D) diabetes. This study explored their potential link in diabetic rat hearts. Methods: Experiments were conducted on T1D and T2D Sprague-Dawley rats induced by streptozotocin and fructose-rich diet, respectively. In T1D, rats were treated with Enalapril (Ena) or Losartan (Los) for six weeks, whereas T2D animals received high-dose (HD) or low-dose (LD) Ena for 8 weeks. Heart function was assessed via echocardiography, Ca2+i transients by Indo-1 fluorometry in Langendorff-perfused hearts, and key Ca2+i cycling proteins by Western blot. Data: mean ± SD. Results: Diabetic hearts exhibited reduced contractile performance that was improved by RAS inhibition both in vivo (ejection fraction (%): T1D model: Control: 79 ± 7, T1D: 54 ± 11, T1D + Ena: 65 ± 10, T1D + Los: 69 ± 10, n = 18, 18, 15, 10; T2D model: Control: 73 ± 8, T2D: 52 ± 6, T2D + LDEna: 62 ± 8, T2D + HDEna: 76 ± 8, n = 9, 8, 6, 7) and ex vivo (+dPressure/dtmax (mmHg/s): T1D model: Control: 2532 ± 341, T1D: 2192 ± 208, T1D + Ena: 2523 ± 485, T1D + Los: 2643 ± 455; T2D model: Control: 2514 ± 197, T2D: 1930 ± 291, T2D + LDEna: 2311 ± 289, T2D + HDEna: 2614 ± 268). Analysis of Ca2+i transients showed impaired Ca2+i release and removal dynamics and increased diastolic Ca2+i levels in both models that were restored by Ena and Los treatments. We observed a decrease in sarcoendoplasmic reticulum Ca2+-ATPase2a (SERCA2a) expression, accompanied by a compensatory increase in 16Ser-phosphorylated phospholamban (P-PLB) in T2D that was prevented by both LD and HD Ena (expression level (% of Control): SERCA2a: T2D: 36 ± 32, T2D + LDEna: 112 ± 32, T2D + HDEna: 106 ± 30; P-PLB: T2D: 557 ± 156, T2D + LDEna: 129 ± 38, T2D + HDEna: 108 ± 42; n = 4, 4, 4). Conclusions: The study highlights the critical role of RAS activation, most likely occurring at the tissue level, in disrupting Ca2+i homeostasis in diabetic cardiomyopathy. RAS inhibition with Ena or Los mitigates these disturbances independent of blood pressure effects, underlining their importance in managing diabetic heart failure.